Voando com gaivotas: um estudo das interações na educação de surdos - Souza, Margarida Maria Pimentel de (2008)
This study aimed to investigate the particular process of teaching and learning, carried over two distincts languages and cultures, this is, a universe formed by a non-deaf teacher and six deaf students. This is a qualitative research developed in an ethnographic approach. For data collecting, I proritized remarks, registering them through reporting and filming due to the spatial-visual aspect of the language of the students. Analyses of the data were focused in the strategies of mediation / interaction and in the discursive activities of the actors of a 4th grade of elementary school in a special school in the city of Fortaleza. The theoretical references are firmed in the historical-cultural vision of Lev Vygotsky, especially with regard to the development and learning as a result of a socio-cultural process as well as the constructs of Mikhail Bakhtin about the principle dialogical, that enhances the occurrence of several voices in the discursive activities, theoretical approaches that bring fundamental reflections about the production of the sign and participation of the other. The results obtained showed that the actors seek multiple strategies such as use of drawings, portuguese flagged, gestures etc. To fill the gaps of the failure meeting in linguistic , especially the students who do not ceased to make hard work of significance. So, I could verify that although be used various materials or symbolic resources, rehearsing a gestural communication, it is the sign language, the support which will serve as an organizer element of the thought of the deaf, as is a standalone system language, with grammatical structure independent, whose combination of parameters allows the preparation of contexts and abstraction. Therefore, based on studies like this and the legislation in the country that recommend the Bilíngüe Education for these actors, it is crucial that be organized pedagogic actions which teaching how to "listen" their hands and their bodies, emphasizing the discursive trading , with the goal of boost the development of such apprentices under the bias bilingual and bicultural.